2000
DOI: 10.1038/sj.onc.1203228
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory interaction of c-Myb and GATA-1 via transcriptional co-activator CBP

Abstract: Gene targeting experiments have revealed that transcription factors such as c-Myb and GATA-1 play crucial roles during hematopoietic di erentiation. c-Myb is necessary in the immature cells of almost every hematopoietic lineage and GATA-1 is essential for the development of the erythroid lineage. In addition, CREB-binding protein (CBP) acts as a transcriptional adapter for various transcription factors, including cMyb and GATA-1. In this paper, we show that the transcription factors c-Myb and GATA-1 each inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Takahashi et al (2000) reported that c-Myb and GATA-1 interact in vitro via their DBDs using a GST-pull down assay and that these proteins could reciprocally inhibit each other's activities on synthetic promoters. It was proposed that this inhibitory effect could be due to the exclusive binding characteristics of !c-Myb and GATA-1 to CBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takahashi et al (2000) reported that c-Myb and GATA-1 interact in vitro via their DBDs using a GST-pull down assay and that these proteins could reciprocally inhibit each other's activities on synthetic promoters. It was proposed that this inhibitory effect could be due to the exclusive binding characteristics of !c-Myb and GATA-1 to CBP.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is likely that interaction between c-Myb and GATA-1 may simply have different effects on different promoters since interaction between c-Myb and GATA-1 might result in different outcomes depending on promoter context. Second, Takahashi et al (2000) used two synthetic promoter fragments, one containing six tandem repeats of the Myb-binding site and the other representing a minimal GATA-1 promoter. These synthetic promoters may not reflect situations on natural promoters where Myb-and GATA-binding sites are located in the same promoter, or when they function via novel DNA sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At ®rst, we con®rmed that the activated MERT could inhibit the transcriptional activation by B-Myb in the context of ES cells. ES cell clones which constitutively expressed ERT or MERT were transfected by lipofection with a Myb responsive reporter gene, 6MBS-Luc, consisting of six tandem repeats of Myb responsive elements and luciferase gene (Takahashi et al, 2000). Then, the transfected ERT and MERT clones were cultured in the presence or absence of 4-OHT.…”
Section: Inhibition Of B-myb Activity By the Activated Mertmentioning
confidence: 99%
“…To activate the MERT and ERT proteins, cells were cultured in the presence of 10 77 M 4-OHT (Sigma) in most experiments except luciferase assay. For luciferase analysis, 2 mg of 6MBS-Luc plasmids (Takahashi et al, 2000) was transfected with Lipofectamine 2000 (Gibco BRL, Rockville, MD, USA) in 6 well plates. 5610 78 M 4-OHT was added 24 h after the transfection and luciferase activity was analysed 48 h after the transfection.…”
Section: Cell Culturementioning
confidence: 99%